Великомасштабна структура Всесвіту, Великий атрактор і спектри збурень - Гнатик, Б.I.; Лукаш, В.М.; Новосядлий, Б.С. (Кинематика и физика небесных тел, 1991)
Рассчитаны корреляционные функции галактик и их скоплений, крупномасштабные потоки галактик, явление типа Великого аттрактора как крупномасштабного пика гауссовского поля возмущений плотности, а также анизотропия температуры реликтового излучения для моделей Вселенной с одним и тремя сортами массивных нейтрино, с холодными частицами, с горячими и холодными, с двойной инфляцией и заданной мощностью на больших масштабах в спектре возмущений плотности. Проанализированы требования к спектру с точки зрения соответствия прогнозируемых и наблюдаемых величин и предложена его аппроксимация. In the frame of cosmological models with random Gaussian density fluctuations, the relations between predicted and observational characteristics of the large-scale structure of the universe are analysed. The calculations of the galaxy and cluster correlation functions, large-scale galaxy streamings, great attractor event as large-scale peak and anisotropy of cosmic microwave radiation are performed for the models of the universe with one and three sorts of massive neutrinos, with cold particles, with hot and cold ones, with double inflation and with additional power in the density fluctuation spectrum. The requirements to the spectrum of density fluctuations are analysed and the spectrum approximation is proposed.